The Chemical and Pharmacological Properties of Mitragynine and Its Diastereomers: An Insight Review - Karunakaran, Thiruventhan; Ngew, Kok Zhuo; Zailan, Ahmad Alif Danial; Mian Jong, Vivien Yi; Abu Bakar, Mohamad Hafizi (Frontiers in Pharmacology, 2022)
Mitragynine, is a naturally occurring indole alkaloid that can be isolated from the leaves of a psychoactive medicinal plant, Mitragyna speciosa also known as Kratom are found to possess a promising analgesic effect on mediating the opioid receptors such as μ (MOR), δ (DOR) and κ (KOR). This alkaloid has therapeutic potential for pain management as it has limited adverse effect compared to classical opioid, morphine. Mitragynine is frequently regarded to behave like opioid but possesses milder withdrawal symptom. The use of this alkaloid as the source of an analgesic candidate have been proven through comprehensive preclinical and clinical studies. The present data have shown that the mitragynine is able to bind to opioid receptors particularly MOR to exhibit the analgesic effect. Moreover, the chemical and pharmacological aspects of mitragynine’s diastereomers, speciogynine, speciociliatine, and mitraciliatine is discussed as it is interesting to know how the difference in stereochemical configuration could lead to the difference in the bioactivity of the respective compounds. Hence, in this review, the updated pharmacological and toxicological properties of mitragynine and its diastereomers are discussed to render a comprehensive understanding of the pharmacological properties of mitragynine and its diastereomers based on their structure-activity relationship study (SARs).